KESANTUNAN BERBAHASA BASISOMBAUDALAM ACARA PULANG BAINDUOK DI DESA MUARA MAHAT BARU KECAMATAN TAPUNG KABUPATEN KAMPAR - Dasma Ranty; Dudung Burhanudin; Hasnah Faizah AR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT :This study discusses civility in text basisombau ulu jambau, ulu tepak dan buka selo. Basisombau is the language used by speakers in conveying the intent and purpose. Basisombau contained in the show home bainduok or looking for tribal events conducted by local communities and indigenous people who are not in the Muara Mahat Baru Village. Politeness is the attitude conveyed by the speaker speaking to opponents said. The method in this research is descriptive method that is based in the fact that there or phenomena that are empirically speakers in the speaker, in this study found the phenomenon of politeness in speaking basisombau. First, the text contained 14 data ulu jambau, have indicators that politeness maxims of wisdom, modesty maxim, agreement maxim, maxim compliment,. Second, the text contained 9 ulu tepak of data, have indicators that politebess maxims of wisdom, maxims agreement, sympathy maxims, maxim praise. Third, in buka selo text are 10 data, , have indicators that politeness maxims of wisdom, agreement maxim. The scale of politeness on 33 data is Indirectness scale,all the data are positive politeness is not independent of the form of speech acts, the context and meaning Keywords :Politeness, Basisombau, Pulang Bainduok( Looking for parts)